2023
DOI: 10.1155/2023/5586664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonmagnetic Doping on Dielectric Properties and Initial Permeability of Ba-Ni Ferrite Nanoparticles by Virtue of Zn2+ Ions

Sadiq H. Khoreem,
A. H. AL-Hammadi

Abstract: The effects of composition, temperature, and frequency-dependent dielectric properties of barium-nickel-based ferrites have been investigated. The conventional ceramic technique prepared the compositions BaNi2-xZnxFe16O27 (at x = 0.0, 0.4, 1.2, and 2). The analysis of X-ray diffraction patterns showed that they were single-phase. The average grain size, lattice constant, and density were found to increase as Zn2+ ion substitution increased. According to the frequency and Zn concentration, the dielectric parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…In general, nickel ferrites preferred to occupy octahedral sites, whereas zinc ferrites prefer to occupy tetrahedral sites. [5]. Within the zinc-substituted Ba (Ni2-xZnx)2Fe16O27, khoreems et al observed that the BaNi-W was as having extremely low permeability, with an increase in permeability and a fall in FMR frequency [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, nickel ferrites preferred to occupy octahedral sites, whereas zinc ferrites prefer to occupy tetrahedral sites. [5]. Within the zinc-substituted Ba (Ni2-xZnx)2Fe16O27, khoreems et al observed that the BaNi-W was as having extremely low permeability, with an increase in permeability and a fall in FMR frequency [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[5]. Within the zinc-substituted Ba (Ni2-xZnx)2Fe16O27, khoreems et al observed that the BaNi-W was as having extremely low permeability, with an increase in permeability and a fall in FMR frequency [6,7]. Infrared spectra across the 400-4000 cm−1 range of frequencies were used to investigate the optical properties of BaNi2−xZnxFe16O27 ferrite.…”
Section: Introductionmentioning
confidence: 99%